A expressão do aspecto habitual : um estudo na fala e na escrita de Itabaiana/SE - Barreto, Eccia Alécia (2014)
This study aims at identifying the traits and the contexts that characterize the habitual aspect occurrence in a sample of speech and writing Itabaiana/SE community in order to contribute to the aspectual descriptive model and support Portuguese language teaching. We begin with a compositional point of view, predicting the interaction between grammatical and lexical components for its expression. In addition, we propose a guided approach by American cognitive functionalism (BYBEE, 2010; GIVON, 2011) combined with the notion of aspectual gradience proposed by Bybee et al. (1994). We understand that linguistic phenomena are derived from cognitive processes and human communication occurs on the basis of experiments involving participants and non-homogeneous contexts (BYBEE, 2010). In order to investigate the traits and contexts that influence the use of habitual aspect within the samples, we controlled the linguistic factors as well as formal, cognitive and discursive character: I) aspectual modifier (presence or absence); II) aspectual traits: durativity [+ / - durative], dynamism [+ / - dynamic], homogeneity [+ /- homogeneous]; III) Vendler s actional classes + cognition + (activity, status, accomplishments, achievements and cognitive); IV) tense - imperfect, past perfect; and other tenses that proved to be relevant to compose the habitual aspect; V) verb: Simple or periphrastic; VI) gradations of modality: degree 1, degree 2, degree 3 and degree 4; VII) specification of reiteration: (+ / - specifiable); VIII) type of textual sequence: narrative, opinionated, descriptive texts and essays; VIX) discourse topic: intertopic level, inter-clausal level and intratopic level; X) agentivity: active and passive subjects. For the study proposed by us, we take the corpus of analysis the following databases: Itabaiana / SE s Intellectual Speakers (ARAUJO; BARRETO; FREITAG, 2012) and Itabaiana / SE s Narrative and Opinionated Texts Writing Database (ARAUJO; PEIXOTO; FREITAG, 2012), which are linked to the Group of Studies in Language, Interaction and Society (GELINS). Data were subjected to statistical analysis, from which we noted that arrangements traits are more prototypical to the expression of habitual aspect in Itabaiana / SE, what may present a proposal for gradience. Thus, 396 contexts of habituation were analyzed. The quantitative data suggest that there were changes in trajectories, which require stages with a reduced stability of the system as there are overlapping forms (PP and IP) that can perform the same function: the expression of habitual aspect. The quantitative results suggest a continuum of shapes PP and PI for the expression of habituation. Besides presenting some peculiarities, stative aspectual modifier + verb + PP update the habitual aspect, in which the situation is seen as unique and durative, uninterrupted in its duration, but being repeated indefinitely, taking into account that its last limits are not visible. Furthermore, the structures with action verbs + PI or aspectual modifier + nonstative verb + PI also update the habitual aspect, therefore, the situation is not perceived as unique, but as repeating indefinitely. Moreover, through Vendler s (1957) decomposition of aspectual classes, developed by Bertinetto (2001), we conclude that stative verbs promote the emergence of habitual aspect in interaction with PP due to its trait [- dynamic] and the presence of aspectual modifier. In contrast, action verbs promote the interaction with PI aspect and, in some cases, with the presence of an aspectual modifier because they share the trait [+ dynamic].